The humanistic care ability of nurses in 27 provinces in China: a multi-center cross-sectional study - He, Xiaoxiao; Wang, Wei; Liao, Lulu; Ren, Yanhong; Liu, Yilan; Xu, Juan (Frontiers in Medicine, 2024)
Currently, studies found that the humanistic care ability of nurses is at low level in China, resulting in patients' concerns and dissatisfaction regarding the lack of empathy among nurses. We aimed to explore the factors that influence nurses' humanistic care ability, providing a new perspective on improving patient satisfaction and promote high quality medical services. Methods A multi-center cross-sectional study recruited nurses from tertiary and secondary hospitals in China between July 2022 and August 2022. Data concerning self-developed questions on nurses' socio-demographic data and Caring Ability Inventory (CAI) were collected through the Questionnaire Star Platform, using a multi-stage sampling method.The total score for the level of caring ability among the 15653 surveyed Chinese nurses was 192.16±24.94. Various factors significantly influence the level of humanistic care ability, including professional title, department, degree of passion for the job, job satisfaction, emphasis on self-care, participation in humanistic care training, support from family for the job, relationships with colleagues, satisfaction with salary, and previous experience working in pilot wards emphasizing humanistic care (P＜0.01).At present, nurses exhibit a comparatively modest proficiency in humanistic care ability.Numerous factors contribute to this situation. Nursing administrators ought to enhance the scope of humanistic care practices, conduct consistent professional training sessions, advocate for the implementation of model wards emphasizing humanistic care, foster a supportive organizational culture conducive to nurses, and underscore the significance of both nurturing nurses and promoting self-care among them.